Computer-based Analysis of the Relationship Between Urban Ecological Land and Urban Competitiveness in Xi'An. Issue 3 (February 2021) - Zhao, Defang
Abstract: The relationship between urban ecological environment and urban competitiveness is getting closer. However, the dynamic evolution relationship is often overlooked. A city is a complex ecosystem, and the social economy is naturally dominated by human activities. As an important part of the urban complex ecosystem, ecological land has important ecological service functions. In the context of rapid urbanization, in order to meet certain development requirements, a large amount of ecological land has been converted into construction land for urban development, such as farmland, wetland, and water. There are problems such as fragmentation of landscapes and decline of land ecological services. Development practice shows that the occupation of ecological land promotes the competitiveness of cities and runs counter to the sustainable development of cities. This paper analyzes computer big data, and uses literature research methods and empirical analysis methods to explore the changing characteristics of urban ecological land and urban competitiveness in Xi'an.